CONTRIBUTION OF INTERNAL FACTORS THAT INFLUENCE THE FINANCIAL PERFORMANCE OF MSMES - Budiasni, Ni Wayan Novi; Ayuni, Ni Made Sri; Pasek, Gede Widiadnyana; Ditami, I Gede Sri; Ardanari, I Gusti Ayu Agung Maesa (International Journal of Application on Economics and Business, 2023)
This research aims to explore the implications of factors within MSME entrepreneurs in Buleleng Regency on the financial performance of MSMEs. Considering not only external factors, but also internal factors. The research results show that financial literacy, financial efficacy positively and significantly influence financial performance with locus of control as an intervening variable. The results of this research were obtained by conducting hypothesis testing using the SEM PLS analysis tool. Apart from indirect effects, direct effects can also be stated that the variables financial literacy, financial efficacy, influence locus of control. Likewise, financial literacy and financial efficacy are related to financial performance. And the locus of control over financial performance is also no less important in making a positive contribution.